HOMOCYSTEINE STATUS OF ELDERLY SLUM WOMEN IN DELHI - Gonmei, Zaozianlungliu; Dwivedi, Supriya; Siddhu, Anupa; Toteja, Gurudayal Singh; Vikram, Naval Kishore; Kamboj, Preeti (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was undertaken to assess homocysteine levels among economically deprived elderly women in Delhi. Methods: The study was carried out among elderly women aged 60â€“70 years residing in Kirti Nagar slums of West Delhi. Blood samples were collected, and serum homocysteine was analyzed using chemiluminescent immunometric assay. Hyperhomocysteinemia was defined as serum homocysteine >15 Î¼mol/l. Dietary information was also collected using 24 h dietary recall method and food frequency questionnaire. Results: The prevalence of hyperhomocysteinemia was 16.9%. The mean serum homocysteine was 12.35Â±6.43 Î¼mol/l. Serum homocysteine levels ranged from 3.84 to 35.20 Î¼mol/l. It was observed that hyperhomocysteinemia was higher in vegetarians (31.2%) compared to non-vegetarians (6.7%). Conclusion: The prevalence of hyperhomocysteinemia is higher among vegetarians than non-vegetarians. Further, research is necessary to see the effect of elevated homocysteine in multiple age-related diseases.